2021
DOI: 10.1121/10.0005274
|View full text |Cite
|
Sign up to set email alerts
|

The effects of native prosodic system and segmental context on Cantonese tone perception by Mandarin and Japanese listeners

Abstract: This study explores the effects of native prosodic system and segmental context on the perception of Cantonese tones by Mandarin and Japanese listeners. In Experiment 1, 13 Mandarin and 13 Japanese subjects took part in a two-alternative forced-choice discrimination test of Cantonese tones in different segmental contexts (familiar vs unfamiliar). In Experiment 2, 20 Mandarin listeners participated in a perceptual assimilation task that examined the cross-language perceptual similarity between Mandarin and Cant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This notion of categorical assimilation is rooted in models of L2 speech learning such as the Perceptual Assimilation Model (Best, 1995; Best and Tyler, 2007) that propose that the ease with which non-native sounds are learned depends on the relative similarity between L1 and L2 sounds. For example, L1 speakers of Mandarin, which only has one high-level tone, appear to struggle with discriminating Cantonese mid-level and low-level tones (Qin and Jongman, 2016; Zhu et al, 2021). It has been suggested that this is because Mandarin listeners tend to assimilate Cantonese level tones to the single Mandarin level tone, making them therefore relatively difficult to perceive accurately (Qin and Jongman, 2016, p. 334; Zhu et al, 2021, p. 4224).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion of categorical assimilation is rooted in models of L2 speech learning such as the Perceptual Assimilation Model (Best, 1995; Best and Tyler, 2007) that propose that the ease with which non-native sounds are learned depends on the relative similarity between L1 and L2 sounds. For example, L1 speakers of Mandarin, which only has one high-level tone, appear to struggle with discriminating Cantonese mid-level and low-level tones (Qin and Jongman, 2016; Zhu et al, 2021). It has been suggested that this is because Mandarin listeners tend to assimilate Cantonese level tones to the single Mandarin level tone, making them therefore relatively difficult to perceive accurately (Qin and Jongman, 2016, p. 334; Zhu et al, 2021, p. 4224).…”
Section: Introductionmentioning
confidence: 99%
“…For example, L1 speakers of Mandarin, which only has one high-level tone, appear to struggle with discriminating Cantonese mid-level and low-level tones (Qin and Jongman, 2016; Zhu et al, 2021). It has been suggested that this is because Mandarin listeners tend to assimilate Cantonese level tones to the single Mandarin level tone, making them therefore relatively difficult to perceive accurately (Qin and Jongman, 2016, p. 334; Zhu et al, 2021, p. 4224).…”
Section: Introductionmentioning
confidence: 99%
“…In phonological-categorical terms too, the rising and falling tones may be relatively easy for Mandarin speakers because these could assimilate in a one-to-one fashion to the Mandarin rise and fall categories. By contrast, the mid-level and low-level tones may be relatively difficult to process because these could assimilate in a many-to-one fashion to the Mandarin high-level or potentially the low-dipping tone (Qin & Jongman, 2016, p. 334; Zhu et al, 2021, p. 4224). As to the phonological similarity with English intonational tone types, the rising and falling tones resemble canonical rising (low-high) and falling (high-low) intonational tone types in Standard Southern British English (SSBE).…”
Section: Methodsmentioning
confidence: 99%
“…This notion of categorical assimilation is rooted in theoretical models such as the Perceptual Assimilation Model (PAM) that propose that the ease with which non-native sounds are learned depends on the relative similarity between L1 and L2 sounds (Best, 1995; Best & Tyler, 2007). For instance, Mandarin-L1 speakers appear to struggle with the discrimination of Cantonese mid-level and low-level tones because they may assimilate Cantonese level tone categories to the Mandarin level tone in a two-to-one fashion (Qin & Jongman, 2016, p. 334; Zhu et al, 2021, p. 4224). Although speakers of English and other non-tonal languages may also assimilate non-native tones to intonational categories, it appears that the effect of such assimilation on L2 tone perception is relatively weak (Reid et al, 2015; So & Best, 2010), arguably because intonational categories have a “weaker (less categorical) mental representation” than lexical tone categories (Francis et al, 2008, p. 269).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, L1 tonal typology has also been shown to affect listeners’ perceptual bias towards different acoustic cues in the perception of tones [ 2 , 18 , 19 ]. It was found that Mandarin and Cantonese listeners paid more attention to the pitch contour, while Japanese listeners attended more to the pitch height [ 19 ]. To the best of our knowledge, Vietnamese is one of the canonical tone languages that has been less studied than others.…”
Section: Introductionmentioning
confidence: 99%